Early Visean bryozoans from the Shishtu II Member, Shishtu Formation, central Iran - Tolokonnikova, Zoya; Yazdi-Moghadam, Mohsen (Geologos, 2014)
Four bryozoan species are described from the upper member (Shishtu II) (Visean, Early Carboniferous = Mississippian) of the Shishtu Formation of central Iran: Nikiforovella ulbensis Nekhoroshev, 1956, Nicklesopora elegantulaformis (Nekhoroshev, 1956), Primorella cf. iranica Gorjunova, 2006, and Nikiforopora intermedia (Nikiforova, 1950). This Visean assemblage shows close palaeogeographical affinities of Iran with Kazakhstan and Russia (eastern Transbaikalia, Kurgan region).